Indigenous Customary Law and International Intellectual Property: Ascertaining an Effective Indigenous Definition for Misappropriation of Traditional Knowledge - Dennis-McCarthy, Nopera (Victoria University of Wellington Law Review, 2020)
The effective protection of indigenous traditional knowledge from misappropriation is a fundamental challenge faced by the intellectual property system. A substantial aspect of this challenge is how the intellectual property regime can practically utilise or incorporate indigenous customary law as a means of protection against misappropriation, when there is an inherent tension between the former and the latter. Any international legal instrument intended to protect against misappropriation of indigenous traditional knowledge will have to contend with this tension: a definition of misappropriation ought to encourage use of local indigenous customary law, but it also must be practically applicable within the confines of the intellectual property system. Consequently, this article considers the challenge in two parts. The first part requires ascertainment of a potential international legal definition of misappropriation that will uphold and maintain indigenous customary law, in the context of the World Intellectual Property Organization (WIPO) Intergovernmental Committee on Intellectual Property and Genetic Resources, Traditional Knowledge and Folklore (IGC) draft articles. To ensure the definition effectively affirms indigenous customary law, it will be based on three key "approaches" to indigenous custom. The second part entails application of the definition to the domestic context, namely through the case studies of New Zealand and Australia, and a subsequent critique of the difficulties of application, to illustrate the challenge of incorporating indigenous customary law within the intellectual property system. This article concludes that the risks inherent in an aspirational definition of misappropriation which may have some challenges in application are outweighed by the potential of normalising and encouraging indigenous customary law as the foundational basis for truly effective protection of traditional knowledge against misappropriation.